Financial Ratio Analysis as a Tool for Measuring the Performance of the Pekanbaru City Regional Budget (APBD) - Suharyono S (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Local Own-Source Revenue (Pendapatan Asli Daerah/PAD) is a crucial component in financing regional expenditures. A decline in PAD and the performance of local governments has a significant impact on the financial performance of the Pekanbaru City Government. This study aims to analyze the financial performance of the Pekanbaru City Government based on fiscal decentralization, regional financial independence, efficiency, effectiveness, and expenditure harmony ratios. The financial ratios employed in this study include the fiscal decentralization ratio, regional dependency ratio, efficiency ratio, effectiveness ratio, and harmony ratio. This research adopts a qualitative approach using a descriptive method. The data consist of primary data obtained through interviews and secondary data in the form of financial statements of the Pekanbaru City Government. Data analysis was conducted using the interactive analysis model developed by Miles and Huberman. The results indicate that the financial performance of the Pekanbaru City Government, as measured by the fiscal decentralization ratio, is categorized as fairly good. The efficiency ratio shows a very efficient level, while the effectiveness ratio reflects performance that has not yet reached an effective level. Furthermore, the calculation of the regional financial independence ratio indicates that the dependency level of the Pekanbaru City Government is relatively low and falls within a consultative relationship pattern. However, operational expenditure still dominates compared to capital expenditure, resulting in less optimal provision of facilities and infrastructure to support improvements in public welfare and the quality of public services.